Teknik Distraksi Sebagai Strategi Menurunkan Kekambuhan Halusinasi - Wicaksono, Marzuki Setyo; , Arum Pratiwi, S.Kp., M.Kes (2017)
Background: the common sign of the patients schizophrenia experience hallucinations. hallucination is the loss of human ability to distinguish internal stimuli (thoughts) and external stimuli (the outside world) so that the client gives the perception or opinion about the object or the environment without any real stimulus. Distraction is to shift attention to another client so it can reduce awareness of pain, and even increases tolerance to pain so pleasant sensory stimuli can stimulate endorphin secretion. Nurses can assess the activities enjoyed or liked by the client so that it can be used to perform distraction. Distraction has been widely used in patients who experience auditory hallucinations. As one of the ways commonly used to fight the hallucinations is to distract commonly referred to (distraction) and relaxation. Hallucinations experienced by clients species vary, but most clients schizophrenia have auditory hallucinations. Auditory hallucinations can be controlled in four ways, namely rebuke hallucinations, taking medication regularly, conversing with others, perform activities scheduled. Objective: The aim of the study is apply distraction technique on the patient with llucination. Methods: The method used was distraction, with case study through interviews ranging from assessment to clients, analyzing the results of the assessment has been done, planned actions that will be given to clients, do the plans that have been made, and to evaluate actions taken. Result: the result of his study is the patient be able to control hallucination by using distraction technique (diversion) to reduce the recurrence of hallucination. Conclusion: nursing problems resolved partially, thus requiring furthertreatment and cooperation with other medical teams, clients and milies that are indispensable for the success of nursing care.There was a decrease in hallucinations experienced by clients efore and after the intervention.